TOKSISITAS EKSTRAK ETANOL KULIT JENGKOL (Pithecelleobium jiringa) TERHADAP LARVA UDANG (Artemia salinia Leach) DENGAN METODE Brine Shrimp Lethality Test (BSLT) - Mega Pratiwi Irawan; Yolanda Yolanda; Zaiyar zaiyar; alfin surya (Klinikal Sains : Jurnal Analis Kesehatan, 2022)
Jengkol plant is one type of plant that is spread in the community and has benefits as an active compound that can be used as traditional medicine. The skin has a variety of benefits, namely it can stop bleeding, cure burns, and as an antiseptic. Jengkol skin contains alkaloids, flavonoids, saponins, tannins and glycosides. The compounds contained in the jengkol bark plant can act as anticancer. The purpose of this study was to determine the toxicity of ethanol extract of jengkol skin (Pithecelleobium jiringa) to shrimp larvae (Artemia salina Leach). The method used was Brine Shrimp Lethality Test (BSLT). The type of research used is quantitative. The results of this study indicate that the ethanolic extract of jengkol peel (Pithecelleobium jiringa) is toxic so it has the potential for anticancer, as evidenced by calculating the concentration log, the LC50 value is 251 ppm. This indicates that the extract is toxic to shrimp (Artemia salina Leach) larvae.